Antimicrobial and antibiofilm efficacy and mechanism of essential oil from Citrus Changshan-huyou Y. B. chang against Listeria monocytogenes. (November 2019) - Guo, Jiajing; Gao, Zhipeng; Li, Gaoyang; Fu, Fuhua; Liang, Zengenni; Zhu, Hui; Shan, Yang
Abstract: Listeria monocytogenes ( L. monocytogenes ) is an important foodborne pathogen which may cause listeriosis and poses potential risks to human health. The aim of this study was to estimate the efficacy of essential oil from Citrus Changshan - huyou Y.B. Chang (Huyou) on both planktonic cells and biofilm against L. monocytogenes, and further to elucidate the potential mechanism of this action. Results showed that Citrus Changshan - huyou Y.B. Chang essential oil (Huyou EO) exhibited significantly in vitro antimicrobial ability against L. monocytogenes, both of scanning electron microscopy (SEM) and transmission electron microscopy (TEM) observations confirmed the physical damage, considerable morphological alteration and the leakage of intracellular constituents. Meanwhile, XTT and crystal violet (CV) assay indicated that Huyou EO was able to destroy preformed biofilm through decreasing the biomass and cellular activity. SEM, confocal scanning laser microscopy (CLSM) and COMSTAT analysis revealed the extensive disruption and architectural changes of biofilm. Moreover, the potential antimicrobial mechanisms were demonstrated by RNA sequencing. Enriched GO analysis identified 8 terms related to cellular components (CC), 50 terms for biological processes (BP) and 21 terms for molecular functions (MF). 35 pathways were significantly enriched in KEGG analysis. The transcriptome analysis offered novel antimicrobial molecular mechanisms of Huyou EO. Highlights: Huyou EO exhibited significant antimicrobial ability against planktonic L. M cells Huyou EO could significantly destroy the preformed biofilm of L.M SEM and TEM results showed the morphological changes of L.M The potential antimicrobial mechanisms were demonstrated by RNA sequencing Huyou EO have great potential to be used as a preservative in food industry